State of the direct reduction and reduction smelting processes - Markotić A.; Dolić N.; Trujić V. (Journal of Mining and Metallurgy. Section B: Metallurgy)
For quite a long time efforts have been made to develop processes for producing iron i.e. steel without employing conventional procedures - from ore, coke, blast furnace, iron, electric arc furnace, converter to steel. The insufficient availability and the high price of the coking coals have forced many countries to research and adopt the non-coke-consuming reduction and metal manufacturing processes (non-coke metallurgy, direct reduction, direct processes). This paper represents a survey of the most relevant processes from this domain by the end of 2000, which display a constant increase in the modern process metallurgy.